Characterization of flavivirus infection in salivary gland cultures from male Ixodes scapularis ticks - Kendall, Benjamin L. (PLoS Negl Trop Dis, 2020)
Infected Ixodes scapularis (black-legged tick) transmit a host of serious pathogens via their bites, including Borrelia burgdorferi, Babesia microti, and tick-borne flaviviruses (TBFVs), such as Powassan virus (POWV). Although the role of female I. scapularis ticks in disease transmission is well characterized, the role of male ticks is poorly understood. Because the pathogens are delivered in tick saliva, we studied the capacity of male salivary glands (SGs) to support virus replication. Ex vivo cultures of SGs from unfed male I. scapularis were viable for more than a week and maintained the characteristic tissue architecture of lobular ducts and acini. When SG cultures were infected with the TBFVs Langat virus (LGTV) or POWV lineage II (deer tick virus), the production of infectious virus was demonstrated. Using a green fluorescent protein-tagged LGTV and confocal microscopy, we demonstrated LGTV infection within SG acinus types II and III. The presence of LGTV in the acini and lobular ducts of the cultures was also shown via immunohistochemistry. Furthermore, the identification by in situ hybridization of both positive and negative strand LGTV RNA confirmed that the virus was indeed replicating. Finally, transmission electron microscopy of infected SGs revealed virus particles packaged in vesicles or vacuoles adjacent to acinar lumina. These studies support the concept that SGs of male I. scapularis ticks support replication of TBFVs and may play a role in virus transmission, and further refine a useful model system for developing countermeasures against this important group of pathogens.